Correction: König et al. Cefiderocol in Critically Ill Patients with Multi-Drug Resistant Pathogens: Real-Life Data on Pharmacokinetics and Microbiological Surveillance. Antibiotics 2021, 10, 649 - Christina König; Anna Both; Holger Rohde; Stefan Kluge; Otto R. Frey; Anka C. Röhr; Dominic Wichmann (Antibiotics, 2021)
1.1 Based on the initial data from Table 1 there were errors in the original article [...]